Avaliação do perfil lipídico dos pacientes obesos antes e após cirurgia bariátrica - Silva, Jose Wellington Santana da (2016)
INTRODUCTION: The mixed dyslipidemia, which is often found in obese patients, is characterized by a set of abnormalities of lipids and lipoproteins in plasma. This includes hypertriglyceridemia, low HDL cholesterol levels, and increase of the cholesterol’s total and LDL-C. OBJECTIVE: The aim of this study is to evaluate the changes in the lipid profile in the pre- and post-bariatric surgery METHODOLOGY: This is a descriptive, retrospective study that reviews the medical files of 200 patients undergoing Bypass technical of bariatric surgery. Lipid levels were evaluated before and after surgery from January 2009 to May 2016. Data such as weight and body mass index (BMI) were included. Data were analyzed using the Kruskal-Wallis one-way analysis of variance (Kruskal-wallis rank sum test) with a significance level of p <0.05. RESULTS: The results are reduction of the average of the parameters weight, BMI, total cholesterol, LDL-C and triglycerides while HDL-C was increased, a desirable effect. CONCLUSIONS: Bariatric surgery provides weight loss and improves metabolic parameters of patients, as well as the lipid profile of patients undergoing this procedure.